The research of the Phlox paniculata L. flowering biological features - A. I. Sokolkina; O. E. Khanbabaeva; V. L. Kudusova; V. N. Sorokopudov (Овощи России, 2024)
Relevance. To meet the demand of the domestic consumer and the effective import substitution of for- eign breeding varieties, Garden phlox (Phlox paniculata L.) needs to breed new varieties with high decorative properties, stability and unpretentiousness. A prerequisite for successful generative reproduction of flowering plants to obtain new forms and varieties is the production of fertile, morphologically complete pollen.Methodology. The purpose of this work is to study the biological features of garden phlox flowering and pollination as part of the breeding process optimization and selecting promising parent pairs. The research was carried out for 2 years (2022-2023) in open ground conditions on the basis of the garden phlox domestic varieties bioresource collection on the territory of the Tsitsin’s Main Botanical Garden of the Russian Academy of Sciences. The peculiarities of the varieties flowering and pollination biology, by assessing the viability of pollen, were studied during the mass flowering phase in 11 varieties selected for their prospects for breeding using methods for assessing pollen viability by staining pollen with acetocarmine and using the M. Alexander method.Results. During the research, a number of garden phlox economically valuable features were established: variability structure of the inflorescence and flower morphology; duration of flowering (35 days or more); different periods of flowering (from mid-June to the end of August); the ability of some varieties to bloom again. It was found that the Alexander’s pollen staining method is more sensitive than acetocarmine staining, and allows for more accurate differentiation of colored pollen grains according to their fertility degree. For artificial pollination and hybridization in phlox, it is recommended to use fresh pollen collected from blooming and fading flowers, since it is in these phases that the pollen fertility index in some varieties exceeded 50% of the total weight. According to the results of the conducted research, the most promising pollinator varieties with a high level of pollen fertility were identified: Skazka (71.2%), Olenka (63.2%) and Gegery (66.7%). The prospect of using the Manon variety as a source of male sterility has been established.